Synthesis and study the Structural and electrical and mechanical properties of High Temperature Superconductor Tl0.5Pb0.5Ba2Can-1Cun-xNixO2n+3-Î´ Substituted with nickel oxide for n=3 - Mohammed, Laheeb. A.; Jasim, Kareem. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
on this research is to study the effect of nickel oxide substitution on the pure phases superconductor Tl0.5Pb0.5Ba2Can-1Cun-xNixO2n+3-Î´ (n=3) where x=(0,0.2,0.4,0.6,0.8.and 1.0). The specimens in this work were prepared with used  procedure of solid state reaction with sintering temperature 8500C for 24 h .we used technical (4-prob)to calculated and the critical temperature Tc . The results of the XRD diffraction analysis showed that the structure for pure and doped phases was tetragonal with phases high-Tc phase (1223),(1212) and low-Tc phase (1202)  and add to the presence of some impure phase. It was noted the value a=b,c  the parameter of  the lattice increment  with the increment of Ni content. The increment of (NiO) concentration effects electrical resistivity, dielectric constant and the hardness.